2009
DOI: 10.1007/s11745-009-3371-x
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Plant and Animal Sterols in Different Oil‐Derived Intravenous Emulsions

Abstract: Intravenous lipid constituents have different effects on various biological processes. Some of these effects are protective, while others are potentially adverse. Phytosterols, in particular, seem to be implicated with parenteral nutrition-associated cholestasis. The aim of this study is to determine the amount of plant and animal sterols present in lipid formulations derived from different oil sources. To this end, animal (cholesterol) and plant (beta-sitosterol, campesterol, and stigmasterol) sterols in seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 21 publications
5
27
1
Order By: Relevance
“…Intravenous lipid emulsions based on vegetable oils also contain significant amounts of the plant sterols b-sitosterol, campesterol, and stigmasterol [22]. Marked accumulation of these phytosterols was found in blood samples of children with PNAC [23], but it remained controversial whether these elevated levels were the cause or consequence of cholestasis [24].…”
Section: Is There a Causal Link Between Intravenous Lipid Infusion Anmentioning
confidence: 99%
“…Intravenous lipid emulsions based on vegetable oils also contain significant amounts of the plant sterols b-sitosterol, campesterol, and stigmasterol [22]. Marked accumulation of these phytosterols was found in blood samples of children with PNAC [23], but it remained controversial whether these elevated levels were the cause or consequence of cholestasis [24].…”
Section: Is There a Causal Link Between Intravenous Lipid Infusion Anmentioning
confidence: 99%
“…Perhaps the widest use of phospholipid emulsifiers is in the application of intravenous nutritional supplementation (5), such as in Intralipid®, a soybean oil/egg lecithin emulsion. However, there may be some disadvantages associated with egg lecithin (or egg PC) as an emulsifier, and advantages to substituting eggderived phospholipids with synthetic phospholipids.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study (6), we found phytosterols to be considerably present in all the lipid emulsions analyzed so as to exceed the amount physiologically absorbed by the gut. In this study, we want to determine the plasma amount of phytosterols deriving from different oil sources in rats receiving parenteral nutrition, and compare it with those in rats on standard oral diet.…”
Section: Introductionmentioning
confidence: 73%
“…Information on the sterol contents of ILEs, however, is currently scant and one of our previous purpose was to identify animal and plant sterols contained in the most representative ILEs. To this end, we selected ILE formulations as being representative in terms of their main oil component (soy, olive oil, fish oil variably combined with mediumor long-chain fatty acids, and purified triglycerides) and we quantified their animal and vegetal sterol contents (6). The relative weight of each sterol, however, varied significantly across formulations, but cholesterol and beta-sitosterol were the most represented followed by campesterol and stigmasterol.…”
Section: Discussionmentioning
confidence: 99%